Targeting PI3K inhibitor resistance in breast cancer with metabolic drugs - Gremke, Niklas; Besong, Isabelle; Stroh, Alina; von Wichert, Luise; Witt, Marie; Elmshäuser, Sabrina; Wanzel, Michael; Fromm, Martin F.; Taudte, R. Verena; Schmatloch, Sabine; Karn, Thomas; Reinisch, Mattea; et al. (Signal transduction and targeted therapy, 2025)
Activating PIK3CA mutations, present in up to 40% of hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (Her2−) breast cancer (BC) patients, can be effectively targeted with the alpha isoform-specific PI3K inhibitor Alpelisib. This treatment significantly improves outcomes for HR+, Her2−, and PIK3CA-mutated metastatic BC patients. However, acquired resistance, often due to aberrant activation of the mTOR complex 1 (mTORC1) pathway, remains a significant clinical challenge. Our study, using in vitro and orthotopic xenograft mouse models, demonstrates that constitutively active mTORC1 signaling renders PI3K inhibitor-resistant BC exquisitely sensitive to various drugs targeting cancer metabolism. Mechanistically, mTORC1 suppresses the induction of autophagy during metabolic perturbation, leading to energy stress, a critical depletion of aspartate, and ultimately cell death. Supporting this mechanism, BC cells with CRISPR/Cas9-engineered knockouts of canonical autophagy genes showed similar vulnerability to metabolically active drugs. In BC patients, high mTORC1 activity, indicated by 4E-BP1T37/46 phosphorylation, correlated with p62 accumulation, a sign of impaired autophagy. Together, these markers predicted poor overall survival in multiple BC subgroups. Our findings reveal that aberrant mTORC1 signaling, a common cause of PI3K inhibitor resistance in BC, creates a druggable metabolic vulnerability by suppressing autophagy. Additionally, the combination of 4E-BP1T37/46 phosphorylation and p62 accumulation serves as a biomarker for poor overall survival, suggesting their potential utility in identifying BC patients who may benefit from metabolic therapies.
Gesehen am 16.07.2025